Regulation of αENaC Transcription - Chen, Lihe (Vitam Horm, 2015)
Aldosterone is a major regulator of Na(+) absorption and acts primarily by controlling the epithelial Na(+) channel (ENaC) function at multiple levels including transcription. ENaC consists of α, β, and γ subunits. In the classical model, aldosterone enhances transcription primarily by activating mineralocorticoid receptor (MR). However, how aldosterone induces chromatin alternation and thus leads to gene activation or repression remains largely unknown. Emerging evidence suggests that Dot1a-Af9 complex plays an important role in repression of αENaC by directly binding and modulating targeted histone H3 K79 hypermethylation at the specific subregions of αENaC promoter. Aldosterone impairs Dot1a–Af9 formation by decreasing expression of Dot1a and Af9 and by inducing Sgk1, which, in turn, phosphorylates Af9 at S435 to weaken Dot1a–Af9 interaction. MR counterbalances Dot1a–Af9 action by competing with Dot1a for binding Af9. Af17 derepresses αENaC by competitively interacting with Dot1a and facilitating Dot1a nuclear export. Consistently, MR(−/−) mice have impaired ENaC expression at day 5 after birth, which may contribute to progressive development of pseudohypoaldosteronism type 1 in a later stage. Af17(−/−) mice have decreased ENaC expression, renal Na(+) retention, and blood pressure. In contrast, Dot1l(AC) mice have increased αENaC expression, despite a 20% reduction of the principal cells. This chapter reviews these findings linking aldosterone action to ENaC transcription through chromatin modification. Future direction toward the understanding the role of Dot1a–Af9 complex beyond ENaC regulation, in particular, in renal fibrosis is also briefly discussed.